2016
DOI: 10.1007/s10719-016-9682-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA-aptamers raised against AGEs as a blocker of various aging-related disorders

Abstract: A non-enzymatic reaction between sugars or aldehydes and the amino groups of proteins, lipids and nucleic acids contributes to the aging of macromolecules, which could impair their structural integrity and function. This process begins with the conversion of reversible Schiff base adducts, and then to more stable, covalently-bound Amadori rearrangement products. Over a course of days to weeks, these early glycation products undergo further reactions, such as rearrangements and dehydration to become irreversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…DNA aptamers have also been produced against advanced glycation end (AGE) products to target macromolecules associated with age related disorders. 161 Although results were promising, it was stated that further testing of the aptamers needed to be performed for safety and efficacy, before consideration for clinical use.…”
Section: Aptamersmentioning
confidence: 99%
“…DNA aptamers have also been produced against advanced glycation end (AGE) products to target macromolecules associated with age related disorders. 161 Although results were promising, it was stated that further testing of the aptamers needed to be performed for safety and efficacy, before consideration for clinical use.…”
Section: Aptamersmentioning
confidence: 99%
“…We have already shown that glyceraldehyde-modified AGEs contribute to diabetic complications in animal models and that their circulating levels are correlated with endothelial dysfunction and inflammatory biomarkers in high-risk patients, including those with diabetes (27,28,36,47,48). Furthermore, in glyceraldehyde-modified AGEs bound to vRAGE with a K d of 8.60 nmol/L (Fig.…”
Section: Limitationsmentioning
confidence: 84%
“…14 Presently, only one aptamer drug (Macugen) has been approved by the FDA, but several others are being evaluated in clinical trials. 15 In addition, aptamers have been used to treat aging-related disorders, 16 obesity and diabetes mellitus, 17,18 cardiovascular diseases, 19 infectious diseases, 20,21 blood coagulation, 22 bone diseases, 23 immunological diseases, 24 and cancers 25 (Figure 2).…”
Section: Use Of Aptamers In Theranosticsmentioning
confidence: 99%